Abnormal Morphology of Blood Vessels in Erythematous Skin from Atopic Dermatitis Patients - Momina Khadija Abbasi, Momina Khadija Abbasi, Nosheen Ali, Ama Tul Naval, Sehrish Naz, Mehak Ali, Fakhra Noureen, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Atopic dermatitis is a lesion of skin that affects the blood vessels originated from the vascular plexus. It is a pruritic inflammatory lesion with continuous relapses in between. It has an unknown etiology with no evidence of interaction between environmental and genetic factors. AD has many manifestations including; allergic skin reactions, rhinitis and asthma. This study will illustrate the morphological changes associated with the person suffering from erythematous skin in AD patients. Methods: It is a case control study which has included 40 participants aged between 20-65 years including 20 AD and 20 healthy patients. Study was conducted between the time period of Dec 2021 to Nov, 2022. Cases included all those patients who were diagnosed with AD from a period of at least 3 months whereas controls were taken by matching the age and race with the cases population. Specimens of skin were collected from all the patients and then observed under a photon microscope. Results: Results of the study states that the patients suffering from AD demonstrate thick, complex vessels of blood causing increased flow of blood within the erythematous as well as non-erythematous skin. It suggests that these morphological changes are not observed in all acute and subacute stages but only in chronic stages. In addition, bifurcation was absent in both the lesions either lichenification or erythematous. Practical implication: This study will help the clinicians to understand the morphological changes that occur in atopic dermatitis patients in order to differentiate them from the normal population. Further, it will help the community to differentiate themselves on the basis of the signs and symptoms associated with Atopic dermatitis patients. Conclusion: Study concluded that these results will be helpful in the development of clinical strategies for the treatment of eczema in AD patients. Keywords: Atopic dermatitis, lichenification, flexuous blood vessels, pruritus, eczema, vascular endothelial growth factor.